Role Conflict Among Women In Intercontinental Bank Plc, Lagos State (Global Journal of Human-Social Science, 2012)
In modern industrial societies, women have taken up jobs that take them away from home for better part of the day and this has aroused interest of several scholars in the social sciences. It is in line with this that this paper examined the reasons for women engagement in formal employment and its eventual consequence on the family. The Role and Liberal feminist theories were used to explain the conflicting role of career women. Data were collected from 108 respondents from Intercontinental Bank Plc selected through multi stage sampling techniques using a self designed questionnaire. The study found that women engage in formal employment in order to increase their family's economic status and that their engagement in formal employment gives them limited time to spend with their families. Women dual roles as wives, mothers and formal sector employees are stressful. It demands that women work twice as hard as their male counterparts in order to excel in both. Men should drop the notion that taking care of the children and over-seeing activities in home to be the sole responsibility of the women and embrace an equal share of these activities.
Keywords: Role conflict; Role Strain; Banking sector; Family; Economy; Childcare